Cognitive Development in Rural Children Age 6-8 Years: Integrating Piaget's Theory and Neurocognitive Perspective - Norman Yulia; Sriyanto Sriyanto (AL-ISHLAH: Jurnal Pendidikan, 2026)
Cognitive development among children aged 6–8 in rural areas is often constrained by limited environmental stimulation, yet few studies integrate cognitive, socio-ecological, and neurocognitive perspectives to explain these disparities. This study aims to analyze how these dimensions interact in shaping children’s cognitive development in rural Indonesia. This research employed an exploratory qualitative case study involving nine children aged 6–8 years, nine parents, and two teachers in a rural area of Banjarnegara, Central Java. Data were collected through semi-structured interviews, observations, and document analysis, and analyzed thematically using integrated coding based on Piagetian, Bronfenbrenner’s bioecological, and neurocognitive frameworks. The findings reveal three distinct developmental profiles based on levels of family stimulation. Children with high stimulation demonstrated stable concrete operational thinking, including conservation, classification, and sustained attention. Those with moderate stimulation showed transitional cognitive patterns with emerging but inconsistent logical reasoning. In contrast, children with low stimulation remained in the preoperational stage, characterized by perceptual reasoning, weak working memory, and limited self-regulation. The results indicate that cognitive development is influenced by the interaction between family support (microsystem), home–school continuity (mesosystem), and executive function capacity. The study highlights that cognitive development in rural children is not solely age-dependent but shaped by the synergy of environmental stimulation and neurocognitive processes. Strengthening family–school collaboration and providing context-based cognitive stimulation are essential to support optimal development in rural educational settings.